(untitled) - Committee on Resources and man of the Division of Earth Sciences (San Francisco, California, 1969)
Peace, population, and resources are the central interlocking variables whose unsatisfactory management threatens our options.
Keywords: Natural resources,Tài nguyên thiên nhiên